a The Influence of Learning Models to Students’ Writing Skill of The Explanation Text in Viii Grade at Junior High School (SMP) - Widiyanti, Nur Maya; Wagiran, Wagiran; Pristiwati, Rahayu (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Learning model is standardization for developing the one's skill and in the interpersonal situations. This study aims to determine the effect of learning models to the test results of the students’ writing skill of the explanation text in class VIII grade at junior high school. This research is an ex-post-facto research. The population of this research is all students of VIII grade at SMP of the 2019/2020 academic year. The sample in this study were students of class VIIIA and VIIIB SMP N 22 Semarang with the amount of 64 students who were taken by cluster random sampling, namely by choosing two classes randomly. Data collection techniques were questionnaires for student learning model data and tests to obtain data on the results of the skill to write explanation text for class VIIIA and VIIIB students. The results showed that (1) students with auditory learning models had the highest average score rather than the others who use visual and other learning models. (2) the learning model in this study has a significant effect on the results of the students; skill to write explanation text. (3) The learning model in this study gives e a large effective contribution 89.9% to the results of the students’ writing skill of explanation text; this proved that the learning model is one of the important factors for the students' achievement in writing skill of explanation text.